2009
DOI: 10.1243/09544054jem1712
|View full text |Cite
|
Sign up to set email alerts
|

Impact of energy efficiency on computer numerically controlled machining

Abstract: Increasing environmental demands from governmental bodies and customers stress the importance of companies improving their environmental performance. The research presented here shows that productivity and cost efficiency improvements can be achieved alongside energy savings in a computer numerically controlled machining environment. This improves the profitability of the companies, but also leads them towards more sustainable and environmentally aware manufacturing; the relationship between machining paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…For example, Chandler investigated modern manufacturing methods and found that they are spectacularly inefficient in their use of energy and materials [48]. Anderberg et al showed that the productivity and cost efficiency improvements can be achieved beyond the energy savings in a computer numerically controlled machining environment [49]. Rexroth has improved energy efficiency of servo drive from the optimization of mechanical systems [50].…”
Section: Green Manufacturing Processesmentioning
confidence: 99%
“…For example, Chandler investigated modern manufacturing methods and found that they are spectacularly inefficient in their use of energy and materials [48]. Anderberg et al showed that the productivity and cost efficiency improvements can be achieved beyond the energy savings in a computer numerically controlled machining environment [49]. Rexroth has improved energy efficiency of servo drive from the optimization of mechanical systems [50].…”
Section: Green Manufacturing Processesmentioning
confidence: 99%
“…Anderberg et al [3] summarized in their research that the development of manufacturing methodologies have resulted in a steady growth of energy consumption in the manufacturing sector. This has resulted in a major concern for the manufacturing industry due to the energy and the associated environmental impact reduction required, in particular carbon emission, as a result of international agreements such as the Kyoto Agreement [3].…”
Section: Manufacturing Energy and Implicationsmentioning
confidence: 99%
“…According to [3], manufacturing processes are generally poorly documented in terms of their energy and ecoefficiency. Often, the fixed energy consumption due to unloaded motors, coolant pumps, controllers, fans, and other peripheral equipments are not taken into account when discussing energy efficiency.…”
Section: Manufacturing Energy and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved industrial energy efficiency is a critical cornerstone in climate change mitigation [3]. Therefore, the manufacturing industry must take responsibility and strive to adopt more energy-efficient and sustainable production techniques [4]. If energy data and information can be more effectively used and analyzed in manufacturing, it will provide considerable insights into energy-saving opportunities [5].…”
Section: Introductionmentioning
confidence: 99%